Evaluation of the Efficacy of OSU-2S in the Treatment of Non-Small-Cell Lung Cancer and Screening of Potential Targets of Action - Mengyuan Han; Xiangran Liu; Sendaer Hailati; Nurbiya Nurahmat; Dilihuma Dilimulati; Alhar Baishan; Alifeiye Aikebaier; Wenting Zhou (MDPI AG, 2024)
(1) Background: OSU-2S is a derivative of FTY720 and exhibits significant inhibitory effects on various cancer cells. There is currently no research on the mechanism of the impact of OSU-2S on NSCLC development. We analysed and validated the hub genes and pharmacodynamic effects of OSU-2S to treat NSCLC. (2) Methods: The hub genes of OSU-2S for the treatment of NSCLC were screened in PharmMapper, genecard, and KM Plotter database by survival and expression analysis. The effect of OSU-2S on hub gene expression was verified by Western blot analysis. The ex vivo and in vivo efficacy of OSU-2S on tumour growth was verified using A549 cells and a xenografted animal model. (3) Results: A total of 7 marker genes for OSU-2S treatment of NSCLC were obtained. AURKA and S1PR1 were screened as hub genes. Significant differences in the expression of AURKA and S1PR1 between normal and lung adenocarcinoma (LUAD) tissues were found in the GEPIA2 database; Western blot showed that OSU-2S could affect p-AURKA and S1PR1 protein expression. OSU-2S significantly inhibited tumour growth in A549 cells and xenografted animal models. (4) Conclusions: Our study confirms the inhibitory effect of OSU-2S on NSCLC, screens and demonstrates its potential targets AURKA(p-AURKA) and S1PR1, and provides a research basis for treating NSCLC with OSU-2S.